KERENTANAN KEBAKARAN PERMUKIMAN PADAT DI KELURAHAN SIDODAMAI KECAMATAN SAMARINDA ILIR KOTA SAMARINDA - Yaskinul Anwar; Lukas - (Universitas Tamansiswa Padang, 2019)
Fire disasters are one of the problems that often occur at densely populated in Samarinda City. Sidodamai Village is one of the villages that had a high density of settlements because it is located in the center of Samarinda City. The object of this study is to determine the level of vulnerability of settlement fires in Sidodamai Kelurahan. Data analysis techniques were carried out using the dignity method which gives value on the regional grid based on the value of the parameter to determine the level of fire vulnerability based on the variable fire potential and the availability of fire fighting facilities. Settlement areas that ware vulnerable to fire, divided into three categories, namely low vulnerability, moderate vulnerability, and high vulnerability. Settlements in Sidodamai Village ware included in the moderate to high category. Areas with moderate vulnerability ware areas that dominate in the Sidodamai Village. Whereas the high vulnerability was only in a small part of the Sidodamai Village. The factor that causes fire vulnerability in Sidodamai Village was the fire potential variable which is difficult to control. This had made Sidodamai Village vulnerable to settlement fires.